“Leadership in Rehabilitation Teamwork: Challenges for Developing Countries” - Uddin, Taslim (Frontiers in Rehabilitation Sciences, 2022)
Physical rehabilitation medicine is a diverse specialty; its main objective is to provide comprehensive rehabilitation involving multiple health care professionals to optimize function and improve the quality of life for people with disabilities. There is an increase in the number of people with disabilities, and people with disabilities in lower income countries do not receive the required rehabilitation. Rehabilitation intervention includes functional assessment, rehabilitation goal setting, composition of the focused team and coordination of the team works, all of which require a highly skilled team leader. No single professional is likely to have all the necessary skills to achieve optimal results alone. There is a knowledge gap between the theory, existing situation, and practice in rehabilitation team functioning. In this short communication challenges for quality rehabilitation services were highlighted, including the importance of the leadership role of team functioning.